Perbandingan Status Kesehatan Gingiva dan Kebersihan Mulut pada Perokok Aktif dan Bukan - Rifa, Rizky; Dewi, Anne Handrini (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
Background: Smoking represents one of inveterate habit in everyday life. Smoking cause some disease for example cardiovascular; lungs cancer; esophagus, laryng, and oral cavity. Smokers have more calculus, plaque, debris, gingivitis, and periodontitis than non smoker.Purpose: The purpose of this research is to know the gingival health status and oral hygiene status between active smoker and non smoker.Research Method: Target design used analytic survey with the approach of cross sectional. This subject is a student in faculty of dentistry UIVIY that include in criteria. This research using 30 subject. Consisted 0f15 smokers and I5 non smokers. Every subject examine the GI and OHIS. The result was analyzed with t-test independent. Conclusion and Result: In the GI and OHIS of active smoker and non smoker there are diï¬‚erence which signiï¬cant cause an the GI and OHIS assess p 0. 05. It means that there are diï¬‚erent on gingival health and oral hygiene health between active smoker and non smoker: Active smoker has less gingival and oral health status than non smoker:Â